Calenduloside E Analogues Protecting H9c2 Cardiomyocytes Against H2O2-Induced Apoptosis: Design, Synthesis and Biological Evaluation - Yu Tian; Yu Tian; Yu Tian; Yu Tian; Yu Tian; Yu-Yang Du; Yu-Yang Du; Yu-Yang Du; Yu-Yang Du; Yu-Yang Du; Hai Shang; Hai Shang; et al. (Frontiers Media S.A., 2017)
Modulation of apoptosis is therapeutically effective in cardiomyocytes damage. Calenduloside E (CE), a naturally occurring triterpenoid saponin, is a potent anti-apoptotic agent. However, little is known about its synthetic analogues on the protective effects in apoptosis of cardiomyocytes. The present research was performed to investigate the potential protective effect of CE analogues against H2O2-induced apoptosis in H9c2 cardiomyocytes and the underlying mechanisms. Sixteen novel CE anologues have been designed, synthesized and biological evaluation. Among the 16 CE anologues, as well as the positive control CE tested, compound 5d was the most effective in improving cardiomyocytes viability. Pretreatment with anologue 5d inhibited ROS generation, maintained the mitochondrial membrane potential and reduced apoptotic cardiomyocytes. Moreover, exposure to H2O2 significantly increased the levels of Bax, cleaved caspase-3, and cleaved PARP, and decreased the level of Bcl-2, resulting in cell apoptosis. Pretreatment with anologue 5d (0.02-0.5 μg/mL) dose-dependently upregulated antiapoptotic proteins and downregulated proapoptotic proteins mentioned above during H2O2-induced apoptosis. These results suggested that CE analogues provide protection to H9c2 cardiomyocytes against H2O2-induced oxidative stress and apoptosis, most likely via anti-apoptotic mechanism, and provided the basis for the further optimization of the CE analogues.